Induction of Labor in an Intubated Patient With Coronavirus Disease 2019 (COVID-19). Issue 5 (November 2020) - Slayton-Milam, Suzanne; Sheffels, Samantha; Chan, Dominic; Alkinj, Bashar
Abstract : BACKGROUND: In the global coronavirus disease 2019 (COVID-19) pandemic, to date, delivery of critically ill pregnant patients has predominantly been by cesarean. CASE: A 27-year-old pregnant woman was admitted to a 166-bed community hospital at 33 weeks of gestation with acute hypoxemic respiratory failure secondary to COVID-19. She underwent mechanical ventilation for 9 days. While ventilated, she underwent induction of labor, resulting in a successful forceps assisted-vaginal birth. She was extubated on postpartum day 5 and discharged on postpartum day 10. The neonate was intubated for 24 hours but was otherwise healthy and discharged home at 36 2/7 weeks postmenstrual age. CONCLUSION: Critically ill patients requiring mechanical ventilation, in this case due to COVID-19, may undergo induction of labor and vaginal delivery when carefully selected. Abstract : Critically ill patients who are on mechanical ventilation may undergo induction of labor and vaginal delivery when carefully selected.